2010
DOI: 10.3945/jn.109.119677
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Zinc Deficiency in Rats Affects Growth and Glucose Metabolism in the Offspring by Inducing Insulin Resistance Postnatally ,

Abstract: Interactions among zinc (Zn), insulin, and glucose metabolism are complex. Maternal Zn deficiency affects maternal carbohydrate metabolism, but the mechanisms underlying changes in glucose homeostasis of offspring are not well understood. Rats consumed Zn-deficient (ZnD; 7 microg/g) or control (ZnC; 25 microg/g) diets ad libitum from 3 wk preconception to 21 d postparturition. Litters were culled to 7 pups/dam postnatally and pups were allowed to nurse their original mothers; after weaning, pups were fed nonpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…Sex-specific effects of maternal Zn restriction on insulin signaling cascades (decreased Akt phosphorylation) in skeletal muscle of female offspring were demonstrated in our previous study (18), and similar effects on liver insulin signaling in female offspring with adequate postnatal nutrition (AN group) were observed in this study. Furthermore, maternal Zn restriction was associated with the depression of hepatic insulin signaling in both male and female offspring in the postnatally overfed group (EN group), suggesting that the combination of maternal Zn restriction and excess available calories/nutrients postnatally may impair downstream insulin signaling.…”
Section: Maternal Zn Restriction and Its Interaction With Postnatal Osupporting
confidence: 89%
See 1 more Smart Citation
“…Sex-specific effects of maternal Zn restriction on insulin signaling cascades (decreased Akt phosphorylation) in skeletal muscle of female offspring were demonstrated in our previous study (18), and similar effects on liver insulin signaling in female offspring with adequate postnatal nutrition (AN group) were observed in this study. Furthermore, maternal Zn restriction was associated with the depression of hepatic insulin signaling in both male and female offspring in the postnatally overfed group (EN group), suggesting that the combination of maternal Zn restriction and excess available calories/nutrients postnatally may impair downstream insulin signaling.…”
Section: Maternal Zn Restriction and Its Interaction With Postnatal Osupporting
confidence: 89%
“…The potentially large number of vulnerable pregnant women with mild Zn restriction worldwide is difficult to estimate but may be a reason for an increase in the development of insulin resistance. In a previous study using a rat model, we observed that maternal Zn restriction caused impaired glucose sensitivity in the offspring (18). However, effects of differences in postnatal nutrition and interactions between maternal Zn restriction and postnatal nutritional manipulations on the offspring were not investigated.…”
mentioning
confidence: 91%
“…A number of studies in animal models have also investigated the effects of micronutrient deficiency in the offspring. Maternal zinc deficiency in rats has been associated with increased leptin levels, insulin resistance, and impaired glucose tolerance in the offspring (233). Similar observations were observed in a rat model of maternal dietary chromium restriction (384).…”
Section: Parental Undernutritionsupporting
confidence: 70%
“…Zinc Deficiency, wide spread in the developing country has been associated with long labour, increases the risk for maternal deaths (King, 2000;Jou, 2010). Several studies across the world have shown that zinc supplementation helps in reducing the complications during pregnancy (Chaffee, 2012;UNICEF, 2014).…”
Section: Educationmentioning
confidence: 99%